Citation and referencing support at an academic library: Exploring student and faculty perspectives on authority and effectiveness - Dawe, Lydia; Stevens, J.; Hoffman, B.; Quilty, M. (2021)
Libraries expend considerable time and effort in providing instructional resources to help students learn the “mechanics” of citation and referencing. However, there are few studies that examine the efficacy of these resources. Using focus group methodology, the authors explored student and faculty perspectives about citation practices through their use of the library’s online referencing guide. It was found that faculty struggled to instill “real world” meaning for students around academic integrity practices, while students reported feeling confused and somewhat intimidated about the scholarly writing process. Findings reveal the importance of situating referencing within a positive, holistic approach to academic integrity that emphasizes critical thinking and student autonomy.